The Impact of Governance Mechanisms on the Accounting Disclosure of the Sustainable Development of Iraqi Economic Units - Nazar Mostafa AL-Sarraf, Sarah; Fadil Al-Taie, Bushra (Journal of Economics and Administrative Sciences, 2022)
The research aims to demonstrate the impact of governance mechanisms on the quality of financial reports in the light of the accounting disclosure for sustainable development represented in (accounting disclosure for economic development, accounting disclosure for environmental development, and accounting disclosure for social development) in a sample of banks listed in the Iraq Stock Exchange. Governance mechanisms were measured by evaluating and analyzing the mechanisms in banks for the research sample consisting of (15) banks, based on the governance guide issued by the Central Bank, as well as the banks’ financial reports for the years 2016 -2018, and the dimensions of accounting disclosure for sustainable development were measured through the use of a form. The survey, which is one of the sources of obtaining data and information related to the accounting disclosure on sustainable development. In preparing the form, the researcher relied mainly on the indicators issued by the (GRI), especially the index (G4), and the form (70) forms were distributed to a sample of bank employees, the sample of the research. The study model and hypothesis were built based on the literature of previous studies, and the simple and multiple linear regression method was used to test the hypotheses. Senior management and lack of transparency in information disclosure and financial reporting, and the most important thing that the research recommends is activating governance mechanisms in banks that have a positive impact on the relationship between accounting disclosure for sustainability. Development, as it limits the opportunistic behavior of management and encourages banks to achieve more transparency in financial reporting.